The Effect of Problem Based Learning Model Assisted by Color Journey Learning Media on Social Arithmetic Material on Students' Learning Motivation - Wulandari, Yunita; Umardiyah, Fitri; Zuhriawan, M. Qoyum (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This research was conducted with the aim of determining the influence of learning motivation of class VII students at SMP Al - Furqon before and after implementing the problem based learning model. The research method used was pre-experimental design with a one-group pretest-posttest design and used a quantitative research approach. . The subject of this research was class VII A of Al-Furqon Middle School. The research instruments used were pre-questionnaires and post-questionnaires as well as test results as supporting data. The questionnaire instrument is in the form of statements regarding pre-questionnaire and post-questionnaire learning motivation to measure students' learning motivation before and after implementing the problem based learning model assisted by ethnomathematics learning media which is supported by student test results. The data analysis technique used is hypothesis testing. However, before carrying out a hypothesis test, the data obtained must first be tested for normality. Based on the calculation of the paired sample t test using IBM statistics 29 which shows that the significance value is 0.001. The significance value shows 0.001 < 0.05 error level, so it can be concluded that Ha is accepted. Acceptance of this Ha means that there is an influence of the problem based learning model assisted by ethnomathematics learning media on social arithmetic material on students' learning motivation.